Animals as Symbols of Human Positive and Negative Traits on Javanese Expressions - Setiawan Prasetyoningsih, Tri Wahyu; Purwaningsih, Dyah Raina; Yulianita, Nadia Gitya (Lingua Cultura, 2020)
The research aimed to analyze the metaphor of animalsâ€™ names in Javanese expressions as representing power and authority in its positive and negative sides. The ancient land of Java was ruled by kings. This situation indicated that ancient Javanese were closely related to kingdoms and regulations that were strict rules of politeness rules or authoritarian. It created a situation where direct criticisms, suggestions, and warnings were conveyed to those who hadÂ power, which might cause the problem to the conveyor. Thus, people preferred to express their opinion in theÂ metaphorical form to preserve the Javanese manners. Since Javanese people also lived as farmers and hunters, they could identify the nature of various animalsâ€™ characters. They began to compare some animalsâ€™ nature characters to describeÂ human characters or behaviors in the forms of metaphor known as Javanese expressions. The methods applied were aÂ descriptive qualitative by choosing the data that contained animal names, classifying them, analyzing the meanings of theÂ expressions, and providing results of the analysis. These metaphorical forms are hitherto known as proverbs and areÂ make used them as philosophy of life. They also used proverbs. The data were taken from â€œSeri Kajian Sastra Klasik 100Â Paribasan Jawa Simpul-Simpul Kearifan Lokal Budaya Jawaâ€ by Bambang Husen Al Marie in 2018. There are 26Â expressions using animal names found in this dictionary. Macan, gajah, and asu are the three animals that are mostlyÂ used as a metaphor to describe human characters within a sovereignty. Heuristic and hermeneutic approaches areÂ applied to analyze the data and to find out the real meaning of the classified data.Â Â